Institutional Research and Human Resources: Partnering to Advance Decision Support for Our Greatest Investment. Issue 185 (2nd February 2021) - Bramblett, Sandra
Abstract: Human resources (HR) represent the most significant investment on most of our college campuses in terms of time and financial resources. The importance of good data about the workforce begins with establishing a need for a new position. That need for data continues with recruiting, hiring, training, promoting, retaining (or not), and retiring faculty and staff. Understanding how institutional research (IR) can provide evidence and decision support for this process should generate considerable returns for campus leadership with increased transactional efficiencies and enhanced strategic decisions. Identifying best practices and new approaches for collaboration between the functions involving human resources and institutional research benefits the institution, their stakeholders, and, ultimately, the faculty and staff.